STRATEGIES FOR SMALL BUSINESS DEVELOPMENT IN THE DIGITAL ECONOMY - Aziza Kalanova (Ecomind Press, 2025)
The digital economy offers transformative opportunities for small business development by enabling global reach, operational efficiency, and customer engagement through digital technologies. This article explores key strategies including digital transformation, online presence, data-driven decision-making, e-commerce integration, and innovation. Emphasizing the importance of agility, cybersecurity, and continuous learning, it outlines how small businesses can thrive in a competitive digital landscape. The paper also discusses the role of policy support and ethical practices in sustainable growth. Ultimately, adapting to the digital economy is not optional but essential for small business survival and success in the 21st century.
Keywords: Digital economy, small business, e-commerce, digital transformation, business development.